Response of late sown maize (Zea mays) to organic nutrient sources and rate of application in fragile ecosystem of Meghalaya in acidic soil - Amit A. Shahane; U. K. Behera (Annals of Agricultural Research, 2025)
The field experiment was conducted at Instructional Farm of College of Agriculture (CAU-I), Kyrdemkulai, Meghalaya during kharif season of 2020-21 to study the response of late planting of maize to different sources and rate organic manure (poultry manure, neem cake and Azotobacter).The experiment was planned in randomized block design with eleven treatments consisting of combination of rates and sources of organic manure in maize (DA-61-A). Results showed that, application of poultry manure (PM) or neem cake (NC) equivalent to 100 % N (120 kg N /ha) remain on par with PM (100 % N) + NC (100 % N) in all studied growth attributes. Application of Azotobacter + PM (50 % N) or NC (50 % N) found to increase plant height and dry matter accumulation than application of PM (50 % N) or NC (50 % N) alone. Dry matter portioning at harvest showed that, out of total plant biomass at harvest, 57 to 59.5 % is accumulated in cob and order of significance of dry matter accumulation was cob > stem > leaf > root > tassel. Our study also showed that, crop performance was sub-optimal in late planting condition and maize cobs can’t able to fill with grain and showed rottening mainly due to abiotic stresses such as rainfall and infection by fungal growth.